2021
DOI: 10.1007/s10147-021-01863-6
|View full text |Cite
|
Sign up to set email alerts
|

The mortality rate of COVID-19 was high in cancer patients: a retrospective single-center study

Abstract: Background Coronavirus disease 2019 has quickly turned into a global pandemic with close to 5 million cases and more than 320,000 deaths. Cancer patients constitute a group that is expected to be at risk and poor prognosis in COVID pandemic. We aimed to investigate how cancer patients are affected by COVID-19 infection, its clinical course and the factors affecting mortality. Methods In our single-center retrospective study, we included cancer patients with laboratory confirmed COVID-19 in our hospital. Demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 21 publications
3
43
0
1
Order By: Relevance
“…The global pandemic of coronavirus disease (COVID- 19) has resulted in about 3.85 million deaths world-wide as of June 2021, with the estimated fatality rate among infected patients between 1.5-2.1% 1 . Emerging data demonstrate higher mortality rates among certain high-risk populations with significant co-morbidities, such as organ transplant recipients 2 and cancer patients [3][4][5] . Evidence shows that patients with hematological malignancies are the most vulnerable cancer population [3][4][5][6][7] , with a higher risk for hospitalization and mortality following exposure to the virus 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global pandemic of coronavirus disease (COVID- 19) has resulted in about 3.85 million deaths world-wide as of June 2021, with the estimated fatality rate among infected patients between 1.5-2.1% 1 . Emerging data demonstrate higher mortality rates among certain high-risk populations with significant co-morbidities, such as organ transplant recipients 2 and cancer patients [3][4][5] . Evidence shows that patients with hematological malignancies are the most vulnerable cancer population [3][4][5][6][7] , with a higher risk for hospitalization and mortality following exposure to the virus 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data demonstrate higher mortality rates among certain high-risk populations with significant co-morbidities, such as organ transplant recipients 2 and cancer patients [3][4][5] . Evidence shows that patients with hematological malignancies are the most vulnerable cancer population [3][4][5][6][7] , with a higher risk for hospitalization and mortality following exposure to the virus 7 . Estimated odds ratios (ORs) for mortality are reported to vary between 2.09 and 12.16, depending on the type of malignancy and whether the disease has been actively treated within the months preceding the infection 5,6,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…With around 17 million new cancer cases diagnosed worldwide in 2018 [2] alone, the magnitude of possible SARS-CoV-2 consequences in the field of oncology can be very intimidating. Along these lines, several studies have documented a significantly higher risk for severe COVID-19 events among cancer patients compared with non-cancer individuals [3][4][5][6][7][8][9][10]. The UK Coronavirus Cancer Monitoring Project and the collaboration of 19 European cancer centers recently reported death rates of 28% and 33.6% in 800 and 890 oncological patients with COVID-19, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Other centers have also reported low rates of COVID-19 infection while on systemic therapy [24]. In contrast, some studies suggest that mortality is higher in patients having received active cancer treatment [17,25,26]. A large case-control study including over 73 million electronic medical records reported patients with cancer had significantly higher risks of COVID-19 infection and worse outcomes [21].…”
Section: Covid-19 and Risks In Cancer Patientsmentioning
confidence: 99%